Factors influencing emerging competencies among professional accountants in the cyber era: Malaysian evidence / Zairul Nurshazana Zainuddin … [et al.] - Zainuddin, Zairul Nurshazana; Ahmad, Mahfuzah; Abdul Latif, Nurul Ezhawati; Mohamed Yusof, Faizal; Sulaiman, Suzana (UiTM Press, 2023)
The recent rise of big data, cloud computing, artificial intelligence, and blockchain technology is a wake-up call for the accounting profession. They face numerous challenges in adapting to the demanding cyber era. This study was conducted to examine the internal and external factors that drive the emerging competencies among professional accountants in Malaysia. A qualitative approach was employed with a semi-structured interview conducted with companies awarded Graduates’ Choice Awards, Company of The Year, Best Workplace Practices Award and Corporate Social Responsibility Leadership Award in recent years. This study found that internal factors such as the company’s vision, leadership change, individual achievement indicators, technology and business process are the main contributors influencing the changes in the accounting function. On the other hand, external factors such as political issues, the requirement to respond to green the environment, and the COVID-19 pandemic have caused the emergence of competencies among professional accountants. The competencies include soft skills, empathy, analytical, leadership, communication, emotional intelligence, integrity, and flexibility. This is consistent with the stakeholder theory by Freeman, which explains that different stakeholders’ expectations lead to changes in how organisations operate. Indirectly forcing the accounting profession to respond accordingly.